Evaluation Of Mean Platelet Volume, Red Cell Distributed Width And Neutrophil To Lymphocyte Ratio In Conversion Disorder - Büyükaslan H (Dove Medical Press, 2019)
Hasan Büyükaslan,1 Mehmet Asoğlu2 1Department of Emergency Medicine, Harran University Medical Faculty, Sanliurfa, Turkey; 2Psychiatry Department, Harran University Medical Faculty, Sanliurfa, TurkeyCorrespondence: Hasan BüyükaslanDepartment of Emergency Medicine, Harran University Medical Faculty, Sanliurfa, TurkeyTel +90 530 644 6845Email hasanbuyukaslan@hotmail.comBackground: The pathophysiology of conversion disorder (CD) is still not fully established. Many psychiatric disorders are known to be associated with inflammatory processes. We aimed to compare the routine hemogram values of CD patients with those of the participants in the healthy control group, to assess the inflammation levels of the two groups.Methods: This study was conducted with CD patients (n=158) and healthy controls (n=145). Routine hematological parameters were examined in each participant. Group comparisons were made with Mann–Whitney U-test and Student’s t-test. Regression analysis and receiver operating curve (ROC) analysis were also performed for the analysis of independent predictors.Results: The comparisons revealed that while neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), platelet, neutrophil, red cell distribution width (RDW), and mean platelet volume (MPV) were significantly higher in CD group (P<0.05), lymphocyte was decreased in that group (P>0.05). Multivariate and ROC analyses showed MPV, RDW, and NLR as independent predictors (P<0.05). ROC curve showed that MPV values of 7.8 or above could predict the CD with 84% sensitivity and 85% specificity (area under curve [AUC]=0.878; 95% confidence interval [CI]: 0.817–0.939), RDW values of 11.0 or above could predict the CD with 82% sensitivity and 73% specificity (AUC=0.871; 95% CI: 0.815–0.926), and NLR values of 1.8 or above could predict the CD with 85% sensitivity and 78% specificity (AUC=0.865; 95% CI: 0.802–0.929).Conclusion: CD is related to the acute inflammatory process. MPV, RDW, and NLR can reflect this inflammation. These parameters could be used in differential diagnosis; increased RDW and MPV levels can be used as a novel marker in CD.Keywords: conversion disorder, inflammation, hematologic tests